Penerapan Model Pembelajaran Kooperatif Tipe TGT (Team Game Tournament) Dalam Meningkatkan Keterampilan Berhitung Siswa Pada Pembelajaran Matematika Kelas IV SDN 7 Bandar Jaya - Eka Yunita; Masrurotul Mahmudah; Fadilah, Lutfi (Berkala Ilmiah Pendidikan, 2024)
This research aims to determine the development and feasibility of the quality of the Make A Match Model Puzzle media in thematic learning material on recognizing symbols and Pancasila principles in class I MI Minhadlul Ulum Trimulyo. This research is Research and Development (R & D) research. The method used in this research is a method developed by Reiser & Mollenda which consists of five steps, namely 1) analysis, 2) design, 3) development, 4) implementation, 5) evaluation. This research was conducted in class I at MI Minhadlul Ulum involving 17 students consisting of 9 students and 8 female students. Based on the results and discussion, it can be concluded that the puzzle media was chosen by adapting the make a match learning model to material on symbols and Pancasila principles which were designed using the Corel Draw application and printed using quality duplex paper. The validation results from media expert validators obtained a percentage of 93.3%, which is included in the very good criteria. Material expert validation obtained a percentage of 95.00%, which is included in the very good criteria. And the learning outcomes of students before applying the puzzle media obtained a percentage of 52%, then after the researchers applied the puzzle media the learning outcomes obtained a percentage of 90%, meaning that the effectiveness of using the make a match model of puzzle media was very good to apply.